Esophageal Gastrointestinal Stromal Tumor. Issue 1 (January 2015) - Robb, W. B.; Bruyere, E.; Amielh, D.; Vinatier, E.; Mabrut, J. Y.; Perniceni, T.; Piessen, G.; Mariette, Christophe
<x xml:space="preserve">Abstract</x> Objective: The primary objective was to evaluate the feasibility of surgical enucleation of esophageal gastrointestinal stromal tumors (E-GISTs). Secondary objectives evaluated (i) the impact of tumor enucleation on oncological outcomes, (ii) the effect of pretherapeutic biopsy on the feasibility of E-GIST enucleation, and (iii) the impact of mucosal ulceration on outcome. Background: E-GISTs are very rare tumors and esophageal resection has been the recommended approach. The feasibility and impact on outcomes of tumor enucleation are unknown. Methods: Through a large national multicenter retrospective study, 19 patients with E-GISTs were identified between 2001 and 2010. Patients who underwent either enucleation or esophagectomy were compared. Results: Of over 19 patients identified with E-GISTs, curative treatment was surgical for 16 patients, with enucleation in 8 and esophagectomy in 8. In the enucleation group, median tumoral diameter was 40 mm (18–65 mm), without any mucosal ulceration, preoperative capsular ruptures, or incomplete resections. In the esophagectomy group, the median tumoral diameter was 85 mm (55–250 mm), with mucosal ulceration in 4 patients, preoperative capsular rupture in 1, and no incomplete resections. Severe postoperative complication rates were 50% and 25% in the esophagectomy and enucleation groups, respectively, with 2 postoperative deaths after esophagectomy. After a median follow-up of 6.4 years, 2 recurrences were observed after esophagectomy versus 0 after enucleation. Endoscopic biopsies did not expose patients to complications or local recurrence after enucleation. Endoscopic mucosal ulceration was associated with more aggressive tumors. Conclusions: E-GIST enucleation seems safe for tumors of less than 65 mm in diameter.